ANALISIS STRATEGI PELAYANAN ISLAMI PT. PEGADAIAN (PERSERO) UNIT PEGADAIAN SYARIAH SIMPANG LIMA DI KABUPATEN BANYUWANGI - Yeni Rokhilawati; Ziyadatun Ni’mah (Jurnal Ekonomi Syariah Darussalam, 2020)
Sharia Pawnshop is a sharia non-bank financial institution that has a vision and mission as a company to solve problems without problems, to analyze Islamic service strategies using SWOT analysis to determine internal and external factors. The purpose of this study is to determine the Islamic service strategy adopted by PT. Pegadaian (Persero) Simpang Lima Syariah Pawnshop Unit in Banyuwangi Regency. In this study uses a qualitative approach and uses qualitative research case studies and uses primary and secondary data sources. Data collection methods in this study were interviews, observation and documentation. The data analysis technique is the SWOT analysis technique. Data validity uses source triangulation. The results showed that the Islamic service strategy applied in the Islamic pawnshop there are several types of services including Islamic Shari’a services, services in the Islamic view seen from the results of the SWOT analysis consisting of IFAS matrix namely strengths and weaknesses and EFAS Matrix namely opportunities and threats so that it will show results from a SWOT.